Applying the Institutional Theory at the Level of Halal Consumers: The Case of Cape Town in South Africa. Issue 5 (13th June 2019) - Bashir, Abdalla Mohamed
ABSTRACT: The institutional theory, especially at an individual level, has not been conducted on halal consumers in South Africa. The purpose of this study was to evaluate the degree to which halal consumers who have higher institutional pressures are more expected to purchase halal food products. This study draws upon institutional theory to present empirical evidence that institutional factors may show a significant effect on halal consumer's purchase intention and buying behavior toward purchasing halal food products. A sample of 298 halal consumers in South Africa was selected. Data samples were collected via self-administrated questionnaires. Structural equation modeling (SEM) was used to test study hypotheses. The study showed that all institutional factors have a direct effect on halal consumer's intention and indirect effect on buying behavior. Based on the results, normative pressures had a high significant effect among institutional pressures, followed by other factors such as mimetic and coercive pressures, respectively. This study is first of the uncommon studies examining halal consumers' purchase intention and buying behavior in a non-Muslim country, employing the institutional theory in the context of halal food consumption.